And then what happened, Paul Revere? - Fritz, Jean.; Tomes, Margot (New York : Coward, 1973)
Describes some of the well-known as well as the lesser-known details of Paul Revere's life and exciting ride.
Keywords: Revere, Paul, -- 1735-1818 -- Juvenile literature; Revere, Paul, -- 1735-1818.; United States -- History -- Revolution, 1775-1783 -- Biography